Elemental Abundance Analyses with DAO Spectrograms - XXIX. The Mercury-Manganese Stars 53 Tau, beta Tau, Gamma Crv, and Upsilon Her - Adelman, S. J.; Çalışkan, H.; Gulliver, A. F.; Teker, Ayşegül (EDP SCIENCES S A, 17, AVE DU HOGGAR, PA COURTABOEUF, BP 112, F-91944 LES ULIS CEDEX A, FRANCE, 2006)
We performed elemental abundances analyses of the mercury-manganese (HgMn) stars 53 Tau, beta Tau, and gamma Crv consistent with previous studies of similar stars in this series. The derived v sin i values for the last two stars are 59 and 32 km s(-1), respectively, both of which are greater than those of HgMn stars previously Studied. For 53 Tau this analysis using Selected wavelength regions replaces one performed with coadded photographic spectra. A stricter upper limit is placed on any Hg II lambda 3984 line. The abundances of beta Tau are usually greater than those of gamma Crv. But the later star has a Hg II lambda 3984 line which the former lacks. Our analysis of v Her, which was performed with spectrograms obtained with CCD detectors, is extended by using additional spectrograms to increase the range of wavelengths covered longward of lambda 4800. Minor changes in the derived abundances result.
Keywords: stars : abundances; stars : individual : 53 Tau; stars : individual : beta Tau; stars : individual : gamma Crv; stars : individual : upsilon Her; stars : chemically peculiar; singly ionized silicon; peculiar b-stars; A Type Stars; Oscillator-Strengths; Transition-Probabilities; Rotational Velocities; Term System; Hgmn Stars; Y-II; Solar Abundance; Yıldız: Bollukları; Yıldız : Bireysel: 53 Tau; Yıldız : Bireysel : Beta Tau; Yıldız : Bireysel : Gama Crv; Yıldız : Özgü Kimyasal; Tek Başına Iyonize Silikon; Osilatör-Güçlü; Geçiş Olasılıkları; Dönme Hızları; Vadeli Sistem; Güneş Bolluk